The Mediating Effect of Psychological Empowerment in the Relarionship Between Transformational Leadership with work Engagement and Organizational Research Universities - Mohammed Abdulrab Mohammed Alsenwi (Universiti Sains Islam Malaysia, 2024)
Research on psychological empowerment has received attention among scholars, particularly in the field of management. One of the reason is because psychological empowerment can influence employees’ work attitude and behaviour. However, the discussion about this issue in the context of higher education is still limited, particularly in the context of Research Universities in Malaysia. Therefore, this study is conducted to address this gap. Specifically, this study examines the effect of transformational leadership on psychological empowerment, work engagement, and organizational citizenship behaviour. This study also tests the impact of psychological empowerment on work engagement, and organizational citizenship behaviour. Finally, this study explores the role of psychological empowerment as a mediator in the relationship between transformational leadership, work engagement, and organizational citizenship behaviour. The data of this study have been collected through a survey among 385 academic staff who work in the Malaysian Research Universities (Universiti Malaya, Universiti Sains Malaysia, Universiti Kebangsaan Malaysia, Universiti Putra Malaysia, and Universiti Teknologi Malaysia). Partial Least Squares (Smart-PLS) software was used to analyse the data and to test the hypotheses of this study. The results indicated that there was no significant effect of transformational leadership on work engagement. However, transformational leadership was found to have a positive and significant effect on psychological empowerment and organizational citizenship behaviour. It was also found that there was a positively and significant influence of psychological empowerment on work engagement and organizational citizenship behaviour. Most importantly, psychological empowerment found to be fully mediated the relationships between transformational leadership and work engagement, and it partially mediated the relationship between transformational leadership and organizational citizenship behaviour. The results of the current study have important implications for leaders in Malaysian higher education institutions in general and in Malaysian Research Universities in particular. Based on the results, the study suggests that leaders in Malaysian Research Universities have to adopt the strategy of enhancing psychological empowerment of the academic staff in order to maintain high level of work engagement and a high sense of citizenship behaviour to universities. This will enhance the performance and effectiveness of higher education in the Malaysian context.